Combustion of high carbon (C7-C8) alcohol fuels in a reactivity controlled compression ignition (RCCI) engine as low reactivity fuels and ANN approach to predict RCCI emissions - Okcu, Mutlu; Firat, Mujdat; Varol, Yasin; Altun, Sehmus; Kamisli, Fethi; Atila, Orhan (Elsevier Sci Ltd, 2022)
High carbon alcohol fuels such as heptanol (C7) and octanol (C8) have recently attracted attention among alternative fuels due to their high oxygen content, cetane number and energy density and their production using sustainable pathways in comparison to other common alcohols. Thus, their addition to reactivity controlled compression ignition (RCCI) combustion are also expected to improve the efficiency and pollutant emissions as they have proven in conventional diesel combustion. In present study, the effect of higher carbon alcohols heptanol and octanol as low reactivity fuel (LRF) on RCCI combustion was evaluated in a modified single cylinder DI engine in comparison to conventional combustion mode fed by diesel B7 fuel. Experiments were carried out at varying engine loads from 0% to 60% of max engine torque with 20% intervals under constant engine speed of 2400 rpm and different premixed ratios of LRF (Rp, %0 to %60 at 15% intervals). Artificial Neutral Network (ANN) was also applied to predict the exhaust emissions from RCCI combustion with an estimation error below 6%. The highest increase in cylinder pressure at all loads occurred to be approximately 40% at 0.45 Rp and at 60% load when C8 alcohol was used. The highest heat release rate (HRR) came out to be approximately 111% at 0.60Rp and at 60% load by using C7 alcohol. In general, RCCI was successful in reducing NOx emission and smoke opacity at all premixed ratios of heptanol while higher CO and uHC emissions were observed at all loads when compared with conventional combustion. The greatest reduction in NOx emissions was achieved to be 58% at 20% load and 0.60Rp of heptanol while in smoke opacity, it was calculated as 92% at 60% engine load and 0.60Rp by using octanol. The heptanol RCCI was found to be more effective than octanol in reducing NO(x )emission while the octanol/diesel RCCI exhibited less uHC emissions.
Keywords: RCCI engine; Higher alcohols; Emissions; ANN